PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIMBAH BUAH PEPAYA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Solanum lycopersicum L) - Sonia hamid hamid; husnarika febriani; efrida pima sari tambunan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to determine levels of nutrients N, P, K, C- organic and ratio of C/N on papaya fruit liquid organic fertilizer, knowing the effect of giving papaya fruit liquid organic fertilizer on growth and yield tomato plants (Solanum lycopersicum L) and find out the optimal concentration of liquid organic fertilizer of papaya waste on the growth anad yield of tomato plants (Solanum lycopersicum L). This research was conducted at the green house, Faculty of Science and Technology, North Sumatra State Islamic University in November to February 2020. The paraneters used are stem height, Number of leaves, Number of branches, number of flowers, and number of fruits. This study used a completely randomized design with four treatment and five replication as the trearment used is treatment 0 (0 %) , treatment 1 (10 %), treatment 2 (20 %), treatment 3 (30 %). The highest research results were found in treatment 3 concentrations of 300 %, while treatmen 2 concentrations of 200 % and treatment 1 concentrations of 100 % good growth, while the lowest growth was found in control. Keywords: Tomatoes, Liquid Organik Fertilizer, Papaya Waste.